2004
DOI: 10.1158/1078-0432.ccr-03-0520
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cytotoxicity and Pharmacogenetics of Gemcitabine and Pemetrexed Combination in Pancreatic Cancer Cell Lines

Abstract: Purpose: Gemcitabine is an inhibitor of ribonucleotide reductase (RR) and DNA synthesis and is an effective agent in the treatment of pancreas cancer. The present study investigates whether the multitargeted antifolate pemetrexed would be synergistic with gemcitabine against MIA PaCa-2, PANC-1, and Capan-1 pancreatic cancer cell lines.Experimental Design: Cells were treated with gemcitabine and pemetrexed, and the type of drug interaction was assessed using the combination index. Cytotoxicity of gemcitabine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 22 publications
7
68
1
1
Order By: Relevance
“…The lower dFdCTP synthesis on day 1 would not be secondary to a decrease in gemcitabine membrane transport, due to the higher gemcitabine deamination observed on day 1 and that most of gemcitabine deamination occurs intracellularly, with plasma cytidine deaminase activity playing a limited role . It seems unlikely that the dose of gemcitabine given on day 1 would induce an increase in PBMC deoxycytidine kinase activity, as it has been detected in pancreatic cell lines in vitro (Giovannetti et al, 2004). The pharmacokinetics of DXR during the limited period studied was not affected by gemcitabine when compared with historical controls, similar to the results of other studies (Pérez-Manga et al, 2000;Fogli et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…The lower dFdCTP synthesis on day 1 would not be secondary to a decrease in gemcitabine membrane transport, due to the higher gemcitabine deamination observed on day 1 and that most of gemcitabine deamination occurs intracellularly, with plasma cytidine deaminase activity playing a limited role . It seems unlikely that the dose of gemcitabine given on day 1 would induce an increase in PBMC deoxycytidine kinase activity, as it has been detected in pancreatic cell lines in vitro (Giovannetti et al, 2004). The pharmacokinetics of DXR during the limited period studied was not affected by gemcitabine when compared with historical controls, similar to the results of other studies (Pérez-Manga et al, 2000;Fogli et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…Studies on colorectal cancer cell lines HCT-8, LoVo, WiDr, LRWZ and Calu-1 lung cancer cells showed maximal synergistic cytotoxicity when gemcitabine was followed by pemetrexed in cells (Tesei et al, 2002;Adjei, 2002;Giovannetti et al, 2005). On the contrary, other studies demonstrated that the schedule-dependent synergism was maximal when pemetrexed preceded gemcitabine in HT29 colon cancer cells (Tonkinson et al, 1999), MIA PaCa-2, PANC-1 and Capan-1 pancreatic cancer cells (Giovannetti et al, 2004) and A549 and Calu-6 lung cancer cells (Giovannetti et al, 2005). In vitro experimental data obtained in the present study indicate that in bladder cancer T24 cells the highest chemotherapeutic synergism was observed with the sequence pemetrexed-gemcitabine, while both sequences were almost equivalent in J82 cells.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are in agreement with Table 2 Cell cycle modulation after drug treatments, followed by 24-h culture in drug-free medium. Values (%) are means from three independent experiments and the differences (D) are calculated with respect to controls previous data obtained in colon and pancreatic cells, which were synchronised after 24-h pemetrexed exposure, and showed a significant increase of apoptosis after treatment with gemcitabinepemetrexed combinations (Tonkinson et al, 1999;Giovannetti et al, 2004). One potential antiapoptotic signal transduction system that has been linked to chemoresistance of human cancer cells is the PI3K-Akt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Drug interaction was assessed by treating cells with increasing concentrations of both vinblastine and TBB, at a 1:10 concentration ratio (Vbl:TBB), using the combination index (CI) (Giovannetti et al, 2004), where CIo1, CI ¼ 1, and CI>1 indicate synergistic, additive and antagonistic effects, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Viability was plotted as function of Vbl concentrations (left panel), or TBB concentrations (right panel). Combination index (CI) was calculated as described by Giovannetti et al (2004), where a value o1 indicates synergism.…”
Section: Implication Of Ck2 In the Mdr Phenotype Of Cem Cells G DI Mamentioning
confidence: 99%